2015
DOI: 10.1103/physreve.91.042713
|View full text |Cite
|
Sign up to set email alerts
|

Stepping molecular motor amid Lévy white noise

Abstract: We consider a model of a stepping molecular motor consisting of two connected heads. Directional motion of the stepper takes place along a one-dimensional track. Each head is subject to a periodic potential without spatial reflection symmetry. When the potential for one head is switched on, it is switched off for the other head. Additionally, the system is subject to the influence of symmetric, white Lévy noise that mimics the action of external random forcing. The stepper exhibits motion with a preferred dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(38 citation statements)
references
References 66 publications
3
32
0
Order By: Relevance
“…In Ref. [40] a numerical study was performed that showed how the mechanics of a processive motor protein gets more complicated if the noise from the bath is Lévy distributed. Above, a more basic and general mechanism has been described analytically.…”
Section: Discussionmentioning
confidence: 99%
“…In Ref. [40] a numerical study was performed that showed how the mechanics of a processive motor protein gets more complicated if the noise from the bath is Lévy distributed. Above, a more basic and general mechanism has been described analytically.…”
Section: Discussionmentioning
confidence: 99%
“…In [41], a plot of the interspike intervals and the interevent intervals distributions indicates that neurons and neural network activities are characterized by a non-Gaussian heavy-tail interval distribution, thereby providing a solid reason as to why it makes sense to consider Lévy noise in the study of neural systems. Lévy noise has also been extensively used to model many other complex systems, including lasers [42], quantum dots [43], cardiac dynamics [38], molecular motor [44], economics [45,46], and social systems [47], where changes are often abrupt [48,49]. Furthermore, several studies on stochastic systems have departed from Gaussian to Lévy processes and compared their effects.…”
Section: Introductionmentioning
confidence: 99%
“…In [69], a plot of interspike intervals and interevent intervals distributions indicates that neurons and neural network activities are characterized by a non-Gaussian heavy-tail interval distribution, thereby providing a solid reason as to why it makes sense to consider Lévy noise in the study of neural systems. Lévy noise has also been extensively used to model many other complex systems, including lasers [66], quantum dots [55], cardiac dynamics [60], molecular motor [41], economics [74,2], and social systems [63], where changes are often abrupt [14,87].…”
Section: Introductionmentioning
confidence: 99%